NSRG-18. IMPACT OF MOLECULAR SUBGROUP ON SURGICAL MANAGEMENT OF MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Carai, Andrea; Marongiu, Alessandra; Trezza, Andrea; De Benedictis, Alessandro; Cossu, Silvia; Randi, Franco; Miele, Evelina; Cacchione, Antonella; Colafati, Giovanna Stefania; Camassei, Francesca Diomedi; Mastronuzzi, Angela; Marras, Carlo Efisio
Abstract: We present 47 consecutive patients operated at our Center for medulloblastoma in the last 5 years. Twenty five were males and mean age was 7 years. Eleven patients were infants. Surgery aimed at maximal safe resection in all cases. Molecular subgroup showed 7 WNT, 11 SHH, 14 Group 3, 15 Group 4. We tested a possible correlation between clinical variables relevant for surgery and molecular subgroup (Chi square test, significance = p<0.05). MRI suggested infiltration of the IV ventricle floor mainly in WNT (5/7) and SHH (7/11) tumors. In fact, Group 4 (11/15) and WNT (5/7) tumors were more frequently found to infiltrate brainstem at surgery. Overall, MRI showed low sensitivity (74%) and specificity (70%) in predicting brainstem infiltration. Clinical picture at onset showed a high frequency of hydrocephalus (40/47) independently of subgroup while cranial nerve deficit was more frequent in WNT (4/7) and significantly less frequent in Group 3 (3/14). Post-operative cranial nerve impairment consisted mainly in strabism (24/47) with a single case of facial weakness and were more frequently associated to Group 4 (12/25). Post-operative hydrocephalus requiring shunting was rare (5/47) and independent from molecular subgroup. Brainstem infiltration appeared to be the most relevant feature contributing to surgical complexity and neurological morbidity in medulloblastoma in our series, mostly in Group 4 and WNT tumors. Conversely, Group 3 showed a better neurological post-operative outcome. Further studies are warranted to better define the role of aggressive surgical resection in less aggressive molecular subgroups.